A shrub bending model to calculate the albedo of shrub‐tundra. Issue 2 (5th November 2012) - Ménard, Cécile B.; Essery, Richard; Pomeroy, John; Marsh, Philip; Clark, Douglas B.
Abstract At high latitudes, the albedo and energy budget of shrub‐tundra landscapes is determined by the relationship between the fractional snow cover and the fraction of vegetation protruding above the snowpack. The exposed vegetation fraction is affected by the bending and/or burial of shrubs in winter and their spring‐up during melt. Little is known about the meteorological conditions and snowpack and shrub properties required to cause bending, and few quantitative measurements of bending processes exist. Here, a model combining the few, mostly qualitative, observations available with a biomechanical model representing branches as cantilevers is proposed to provide a first approximation of bending mechanisms. The exposed vegetation fraction is then calculated using structural parameters of shrubs measured at two sites in Canada: the Granger Basin in the Yukon Territory and Trail Valley Creek in the Northwest Territories. The exposed vegetation fraction is in turn used to calculate albedo, which is evaluated against measurements at the two sites. The model considerably improves modelled albedo compared to a model which only buries but does not bend shrubs at TVC, where shrubs become completely buried. However, the model overestimates albedo at GB where only a few shrubs get buried. The bending model is then used to calculate a compression factor for use in a simple parameterization of the exposed vegetation fraction proposed by previous investigators. The parameterization, which is simpler and computationally less expensive than the full model, is evaluated and found to perform well. Despite the need for further developments, the model provides a first approximation of bending processes and contributes to the identification of measurements that are needed in order to improve the model and our understanding of the bending of shrubs. Copyright © 2012 John Wiley & Sons, Ltd.